A survey of libraries of Bible schools belonging to the Philippine Association of Bible and Theological Schools (PABATS) - Siodora, Anastacia V.; Vallejo, Rosa M.; Allen, Jacquelyn (Quezon City Institute of Library Science, University of the Philippines Diliman, 1977)
This is a survey of twenty Bible school libraries which are member of the Philippine Association of Bible and Theological Schools. The libraries surveyed fall under three categories, according to the level of training offered, namely: Bible institutes, Bible colleges and theological schools. A brief history of Bible schools is traced from its inception in America to its introduction in the Philippines. The study includes all aspects of Bible school libraries: their administration and organization, personnel, library resources, services rendered, and facilties.
Conditions in the libraries surveyed reveal much to be desired. Percentage-wise, 75 percent of the libraries represented have sufficient number of books to support their curricular offerings, having fifty books and above per student, five of which have a ratio of over 100 books to a student. However, 25 percent of the participating libraries still need to upgrade their collection. Out of twenty librarians, there is only one MLS degree holder, with less than 50 percent of the librarians in possession of baccalaureate degrees. Cataloging tools are mostly outdated, and half of the respondents had no budgets for their libraries. Results of this inquiry are analyzed, compared and evaluated against accepted standards for libraries, both here and abroad. Weaknesses and strengths are given an objective and unbiased presentation with suggestions and recommendations for improvement, among which are: providing the library with a budget of a least 6 percent of the total institutional budget, allowing the librarian a free hand to use it as he sees fit, encouraging librarians to upgrade themselves and to improve their collection, both in quantity and quality, updating cataloging tools, and setting up professional development programs in schools, for the general improvement of libraries included in this survey.
Mimeographed.
Vita.
Special Problem (Master of Library Science)
Keywords: Libraries, Sunday-school.; PABATS See Philippine Association of Bible and Theological Schools; Philippine Association of Bible and Theological Schools; Theological libraries -- Philippines